2018
DOI: 10.1371/journal.pone.0202279
|View full text |Cite
|
Sign up to set email alerts
|

Organellar genome analysis reveals endosymbiotic gene transfers in tomato

Abstract: We assembled three complete mitochondrial genomes (mitogenomes), two of Solanum lycopersicum and one of Solanum pennellii, and analyzed their intra- and interspecific variations. The mitogenomes were 423,596–446,257 bp in length. Despite numerous rearrangements between the S. lycopersicum and S. pennellii mitogenomes, over 97% of the mitogenomes were similar to each other. These mitogenomes were compared with plastid and nuclear genomes to investigate genetic material transfers among DNA-containing organelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 92 publications
2
20
0
Order By: Relevance
“…The nuclear integrants of organellar DNA were first discovered in a study in which a mitochondrial ATPase subunit gene was found in the nuclear genome, as well as in the mitochondrial genome of Neurospora crassa [25]. Since then, organelle-derived sequences were examined in the nuclear genome of a number of animals [26][27][28][29][30][31][32] and plants [15][16][17][18][19][20][21]. The availability of a large amount of plant organelle and nuclear genome data has made it possible to investigate the prevalence and characteristics of NUMTs and NUPTs in plants.…”
Section: Characterization Of Organellar Dna-derived Sequences In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nuclear integrants of organellar DNA were first discovered in a study in which a mitochondrial ATPase subunit gene was found in the nuclear genome, as well as in the mitochondrial genome of Neurospora crassa [25]. Since then, organelle-derived sequences were examined in the nuclear genome of a number of animals [26][27][28][29][30][31][32] and plants [15][16][17][18][19][20][21]. The availability of a large amount of plant organelle and nuclear genome data has made it possible to investigate the prevalence and characteristics of NUMTs and NUPTs in plants.…”
Section: Characterization Of Organellar Dna-derived Sequences In Plantsmentioning
confidence: 99%
“…NUPTs/NUMTs are usually distributed unevenly in the analyzed plant genomes [20,21,39]. NUPTs and NUMTs are more preferred to distribute in centromeric and pericentromeric regions [36,39], which have few genes and a high level of heterochromatin content [42][43][44].…”
Section: Organization and Distribution Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, given the limited information available about the tomato mitochondrial genome, we identified only a few sites as being affected by SlORRM4 mutations (Yang et al ., 2017). Here, however, based on recently published tomato mitochondrial genome information (Kim & Lee, 2018), we were able to carry out the high‐throughput analysis mentioned earlier to identify mitochondrial C‐to‐U RNA editing sites in tomato fruit genome wide. Consequently, we identified a total of 552 mitochondrial C‐to‐U editing sites in tomato (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing reads were trimmed to remove barcode and adaptor sequences. The clean reads from each library were aligned with the complete tomato mitochondrion reference genome, NC_035963.1 (Kim & Lee, 2018), or chloroplast reference genome, NC_007898.3, using Star (v.2.5.0a, https://github.com/alexdobin/STAR). Then the RNA editing sites and editing extents were analyzed by REDiscover (v.0.14b, https://github.com/lpryszcz/REDiscover).…”
Section: Methodsmentioning
confidence: 99%